Fisher Grading Scale and Cognitive Deficits — Literature Review - Souza, Moysés L. Ponte; Vieira, Ana C.; Azevedo-Filho, Hildo R.C. (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Subarachnoid hemorrhage (SAH) accounts for 5 to 10% of all types of stroke, with rupture of brain aneurysms being related to deficits in memory, executive functions, and language. Changes in brain functions appear to be related to the presence of blood in the subarachnoid space, and the Fisher Scale (FS) correlates the amount of blood identified on computed tomography (CT). This paper presents a literature review of the association of FS with cognitive deficits secondary to aneurysmal subarachnoid hemorrhage (aSAH), using PubMed. The attempt to correlate the amount of blood identified in the CT with the development of cognitive alterations presents conflicting data. It was evidenced that some of the studies did not perform cognitive tests, or did not show differences between the scores of FS due to sample difficulty. The FS, even with its limitations and imperfections, seems to be a safe and easily reproducible way to predict neurological, cognitive or neuropsychological deficits, in view of its routine use when analyzing patients with aSAH.
Keywords: intracranial aneurysm; cognitive dysfunction; subarachnoid hemorrhage; tomography